Faktor Yang Berhubungan Dengan Kejadian Kusta Di Puskesmas Labuha - Suarnianti Suarnianti; Ali Faoji Abubakar; Andi Fajriansih (STIKES Ngesti Waluyo, 2025)
The World Health Organization (WHO) defines leprosy as an infectious disease of mycobacterium affecting the peripheral nerves. Knowledge and personal hygiene affect leprosy cases. This study aims to determine the risk factors associated with leprosy incidence at Labuha Health Center. This research used quantitative research with an observational study design. The study population was 62 leprosy patients at the Labuha Health Center. The sampling used was total sampling technique, with a sample size of 62 respondents (31 respondents in the case group and 31 respondents in the non-case group). The data then analysed using the Kontingency test. The results showed a significant relationship between health knowledge and the incidence of leprosy (p = 0.02 <0.05), the relationship between personal hygiene and the incidence of leprosy (p = 0.02 <0.05), and the relationship between the role of officers and the incidence of leprosy (p = 0.01 <0.05). The conclusion is that there is a relationship between knowledge, personal hygiene and the incidence of leprosy in the Labuha Health Center work area.